People of the book: Fundamental issues of the regulation of Christian, Jewish and Muslim marriage rights - Ištvan Kasuba Robert (Glasnik Advokatske komore Vojvodine)
The relationship between the system of civil matrimonial law and denominational and religious rights in the European context is quite clear to any lawyer because civil matrimonial law evolved from canon law, particularly Catholic canon law. The system of canon law influenced and shaped the thinking of legal scholars who formed civil matrimonial law, and this is also true of Protestant marriage. Jewish and Islamic marriage law, however, differs significantly from the Christian conception and is definitely contractual in nature. This study aims to compare the marriage law rules of Christianity, Judaism, and Islam using the method of comparative law, but it also compares them with the Hungarian matrimonial law system. The study analyzes the pre-marriage procedure and the process of entering into marriage, and it compares the rules for divorce with regard to these three religions. The study is a shorter explanation of one of the important topics of the author's doctoral research since the main topic of the research is facultative civil marriage, i.e. the possibility of recognizing church marriage in civil law in Hungary. The author aims to get a more complete picture of the legal concepts of the three great world religions and the relation of Hungarian marriage law to these religious legal systems.